Empowerment Of Students In An Effort To Improve The Economy Of Islamic Boarding Schools (Case Study of Al-Ittifaq Islamic Boarding School in Bandung and Al-Idrisiyyah Islamic Boarding School Tasikmalaya) - Deden Purbaya; Sutaryat Trisnamansyah; Deti Rostini; Faiz Karim Fatkhullah (IJGIE (International Journal of Graduate of Islamic Education), 2022)
Islamic boarding schools educate students to study religious knowledge, to be skilled and independent when they return from boarding schools to be role models. The general purpose of this research is to find out the empowerment of students in an effort to improve the economy in Islamic boarding schools. This study uses a qualitative approach, descriptive method with observation, interview and documentation techniques. The results showed that the planning of the empowerment of students started from the vision and mission, programs, objectives, stages and strategies of empowerment. Organizing, that each head of the business unit has the responsibility to control, guide, direct and report to the leadership of the pesantren. Santri, alumni and the community are involved in the organizational structure, this placement is adjusted to the abilities and skills possessed. Implementation, refers to a needs analysis, namely what is needed by students, congregations and the community, starting from the leadership example, training, dividing groups according to interests, mentoring, guidance which is a follow-up to the training. Evaluation is carried out according to the situation and conditions but routine activities are carried out weekly, monthly, quarterly, semi-annually. Supporting factors include exemplary leadership, public trust, the location of the limited professional human resources, some are less updated with the times, family innate factors with different backgrounds, the existence of Islamic boarding schools The results of the empowerment of students in both economic boarding schools are increasing and developing.